2019
DOI: 10.3390/pharmaceutics12010015
|View full text |Cite
|
Sign up to set email alerts
|

Both IgM and IgG Antibodies against Polyethylene Glycol Can Alter the Biological Activity of Methoxy Polyethylene Glycol-Epoetin Beta in Mice

Abstract: Pre-existing antibodies that bind polyethylene glycol are present in about 40% of healthy individuals. It is currently unknown if pre-existing anti-polyethylene glycol (PEG) antibodies can alter the bioactivity of pegylated drugs with a single long PEG chain, which represents the majority of newly developed pegylated medicines. Methoxy polyethylene glycol-epoetin beta (PEG-EPO) contains a single 30 kDa PEG chain and is used to treat patients suffering from anemia. We find that the pre-existing human anti-PEG I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…This analysis suggests that pre-existing anti-PEG IgM is not important for ABC and that pegylated interferons and epoetin-beta are most susceptible to ABC induced by anti-PEG IgG antibodies. This is consistent with reports that pre-existing anti-PEG antibodies decrease the anti-viral activity of PEG-interferon-α by accelerating clearance from the blood via uptake into Kupffer cells in the liver and an increased incidence of anti-PEG antibodies in patients who do not respond to PEG-epoetin-beta for the treatment of anemia associated with chronic kidney disease. , …”
Section: Accelerated Blood Clearancesupporting
confidence: 92%
See 2 more Smart Citations
“…This analysis suggests that pre-existing anti-PEG IgM is not important for ABC and that pegylated interferons and epoetin-beta are most susceptible to ABC induced by anti-PEG IgG antibodies. This is consistent with reports that pre-existing anti-PEG antibodies decrease the anti-viral activity of PEG-interferon-α by accelerating clearance from the blood via uptake into Kupffer cells in the liver and an increased incidence of anti-PEG antibodies in patients who do not respond to PEG-epoetin-beta for the treatment of anemia associated with chronic kidney disease. , …”
Section: Accelerated Blood Clearancesupporting
confidence: 92%
“…The amount of anti-PEG antibody required to induce ABC also depends on antibody affinity (Figure B). High-affinity antibodies induce ABC when the molar ratio of anti-PEG antibody exceeds pegylated compound by about 3–10. ,, However, a higher molar ratio is required for low-affinity antibodies: up to 15 low-affinity IgM antibodies and over 90 low-affinity IgG antibodies are required to induce strong ABC of PEG-epoetin-beta in mice . These counteracting factors make estimation of the effects of pre-existing anti-PEG antibodies especially difficult since they possess relatively low affinity for PEG.…”
Section: Accelerated Blood Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, prior studies show that strong ABC is observed when the number of antibodies in circulation exceeds the number of PEGylated compounds ( Xu et al, 2022 ). This trend holds across most PEGylated compounds including proteins, liposomes, micelles, and polymeric nanoparticles and agrees with previous studies showing that three anti-PEG antibodies per PEGylated protein or about 10 anti-PEG antibodies per pegylated liposome are required for ABC ( Shiraishi et al, 2016 ; McSweeney et al, 2018 ; Chang et al, 2019 ). These findings suggest that only compounds dosed at very low molar concentrations ( e.g.…”
Section: Introductionsupporting
confidence: 92%
“…PEGylation is the process of either covalently or non-covalently linking a high-molecular-weight (MW) PEG to an agent (drug or therapeutic peptide/protein), and is commonly used to increase the serum half-life of drugs or proteins/peptides, improve efficacy, and reduce the immunogenicity of the proteins/peptides [ 3 ]. To date, at least 20 PEGylated therapeutics have been approved for use in humans [ 4 ] and most of them have been used in the treatment of various diseases for over a decade.…”
Section: Introductionmentioning
confidence: 99%